Answer:
1) x = 6 and y = -2
2) x = 1 and y = 2
Explanation:
1) x + y = 4...........equ 1
2 x - 3 y = 18 .......... equ 2
x = 4 - y
substituting in equ 2
2 (4 -y) - 3 y = 18
8 - 2 y - 3 y = 18
8 - 5 y = 18
- 5 y = 18 - 8
- 5 y = 10
y = -2
y = -2 put in x = 4 - y
so x = 4 - (-2)
x = 6
therefore x = 6 and y = -2
2) 2 x + 3 y = 8 .....equ 1
-3x -4 y = -11..........equ 2
2x = 8 -3 y
x =( 8 -3 y) ÷ 2
substituting in equ 2
-3{ ( 8 - 3 y) ÷2} - 4 y = -11
- 24 + 9 y- 8 y = -22
- 24 + y = -22
y = 2
If y =2 then x = {8 - (3 × 2)} ÷ 2
x = 1
therefore x = 1 and y = 2